2021
DOI: 10.1186/s41021-021-00189-z
|View full text |Cite
|
Sign up to set email alerts
|

Association of apolipoprotein B XbaI (rs693) polymorphism and gallstone disease risk based on a comprehensive analysis

Abstract: Background Our aim was to investigate the association between XbaI gene polymorphisms in the apolipoprotein B (APOB) gene and gallstone disease (GD) risk through a comparison of the allele and genotype distribution frequencies at this site using meta-analysis. Methods A literature search was performed using PubMed and Wanfang through Jun 1, 2020. Odds ratios (ORs) and 95 % confidence intervals (CIs) were used to assess the strength of associations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…In a meta-analysis of 61 studies including 50,018 subjects, variant allele carriers had high levels of APOB, TG, TC and LDL-C and low HDL-C levels [32]. A meta-analysis including 14 case-control studies showed that APOB rs693 may be a risk factor for gallstone disease, especially in Asians [33]. The SNP rs693 in the APOB gene increased the risk of breast cancer and aortic stenosis among Chinese subjects [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 61 studies including 50,018 subjects, variant allele carriers had high levels of APOB, TG, TC and LDL-C and low HDL-C levels [32]. A meta-analysis including 14 case-control studies showed that APOB rs693 may be a risk factor for gallstone disease, especially in Asians [33]. The SNP rs693 in the APOB gene increased the risk of breast cancer and aortic stenosis among Chinese subjects [34,35].…”
Section: Discussionmentioning
confidence: 99%
“… 36 In a 2021 analysis focused on the XbaI rs693 variant, the presence of this mutation increased the risk of GS disease among the Chinese population, with an OR of nearly 3. 37 This elevated risk remained consistent across both sexes.…”
Section: Genetic Causes Of Cholesterol Gssmentioning
confidence: 68%
“…A significant proportion of these mutations influence cholesterol synthesis or transport in various ways ( Table 1 ). 12 , 14 , 19 , 20 , 23 , 28 , 30 , 31 , 33 35 , 37 , 38 , 40 , 47 , 51 , 52 , 66 71 Notably, the most impactful genes are those belonging to the ABC transporter family, particularly the ABCG8 cholesterol transporter. Different genes play important roles in the pathogenesis of GS disease across various ethnicities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation